Rehabilitation and Conversion of Dar Daikha Constantine - Seghiri-Bendjaballah, Meriem; Kehal, Ikram; Seghiri, Allaoua (Journal of Architecture and environment of child, 2021)
The Ancient Medina of Constantine in Algeria contains an incredible variety of architectural and urban heritage. The traditional house ‘Dar Daikha’ is situated in Souika, the heart of the ancient city, representing a part of Ottoman heritage as well as playing an important role in Constantine’s history. The current deterioration state of Dar Daikha is alarming as it can fall to ruins at any moment. This work aims to preserve the traditional house of Constantine, through the restoration and conversion of Dar Daikha. Visits and observations in situ were done in this study. Adopting the approach outlined by PPSMVSS in its various phases, the physical and functional diagnostic results evaluate the withering of structures due to problems from water and debris, as well as the illicit modifications of the spaces as a result of current daily needs and the bad conservation. The restoration project aims to preserve the house from damage and preserving its functionality. The conversion of Dar Daikha as a guest house assures the preservation of the historical memory, its functional and architectural integrity, and safeguarding of the patrimonial, cultural, and tourism value of the house and the Medina of Constantine.